2014
DOI: 10.1016/j.cct.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

CAPABLE trial: A randomized controlled trial of nurse, occupational therapist and handyman to reduce disability among older adults: Rationale and design

Abstract: Background As the population ages, it is increasingly important to test new models of care that improve life quality and decrease health costs. This paper presents the rationale and design for a randomized clinical trial of a novel interdisciplinary program to reduce disability among low income older adults based on a previous pilot trial of the same design showing strong effect. Methods The CAPABLE (Community Aging in Place, Advancing Better Living for Elders) trial is a randomized controlled trial in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
102
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 117 publications
(107 citation statements)
references
References 55 publications
2
102
1
2
Order By: Relevance
“…37 The participants in this study are part of a well-defined cohort that is taking part in a policy-relevant study, which will evaluate healthcare utilization. 25 Our current study may help clinicians approach patient activation conversations with older adults with functional difficulties.…”
Section: Discussionmentioning
confidence: 93%
“…37 The participants in this study are part of a well-defined cohort that is taking part in a policy-relevant study, which will evaluate healthcare utilization. 25 Our current study may help clinicians approach patient activation conversations with older adults with functional difficulties.…”
Section: Discussionmentioning
confidence: 93%
“…Individuals who were hospitalized three or more times in the prior year, actively receiving cancer treatment or who had expected survival of less than one year, were cognitively impaired, 26 or had plans to relocate within one year were excluded. 10, 23 The Johns Hopkins University Institutional Review Board approved all trial activities, and study participants provided informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…10, 23 In CAPABLE, each older adult and OT collaboratively select up to three goals to address during six program visits of 60–90 minutes, adding additional goals if time allows. Based on these goals, the OT and the older adult prioritize a work order for the handyman.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In prior work (3), we found that participant responses to questions about difficulty and dependence (ie, personal assistance) provide complementary information that together depicts the continuum of disability more fully than does the response to either question alone. These results informed the development of functional scales that have served as disability outcomes in longitudinal studies and clinical trials, with each activity in the scale scored as 0 (no difficulty or need for help), 1 (difficulty but no need for help), and 2 (need for help) (17)(18)(19)(20). In the Women Health and Aging Study II, an additional category of modification, which was intermediate to difficulty and no help, was found to predict the subsequent need for personal assistance (21).…”
mentioning
confidence: 90%